ANALISIS KETERKAITAN DAN PENGGANDA EKONOMI KARET INDONESIA - Alfiah, Tutik; Arifin, Bustanul; Abidin, Zainal (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This study aims to (1) analyze the relationship between rubber and other sectors, (2) determine the multipliers effect of rubber sub-sector on output, household income and added value. This research used Grimp to analyze the impact of the rubber sub-sector of the Indonesian economy. The results showed that (1) backward linkages of rubbers to the input providers sectors relatively high although tended to be conctreated on the railway transport sector, public administration, social services, land transportation and rubber sector itself, (2) increase all of those part which created by rubber plantation dominantly enjoyed by rubber plantation dominantly enjoyed by textile industry, clothes & leather than rubber plantation itself, (3) rubber plantations have a coefficient multiplier output, added value and household income which relatively large, indicated rubber plantations was relatively large in encouraging the creation of output, added value, and household income in Indonesian economy. Keywords: added value, analysis input-output, multipliers effect, rubber